(untitled) (Comparative & International Education Series, 2021)
Online and distance learning is not new to global higher education, as different versions and modalities have existed for several decades. However, COVID-19 forced instructors who had never planned for e-learning to suddenly prepare for and execute a massive shift to online education. The forced shift to e-learning provides an opportunity to reframe instructional modality as a collection of instructional practices as opposed to exclusive categories of face-to-face, hybrid, and online. The pandemic forced open a window to help inform instructors and students about the benefits and struggles of e-learning, as well as tested our assumptions about students’ technology access and literacy. This chapter will examine the potential of e-learning and reflect on how the pandemic may impact the way that instructional modality is understood and leveraged moving forward.